INNOVATIVE MODELS OF AGRICULTURAL SECTOR DEVELOPMENT: FROM FUNDING SCIENTIFIC RESEARCH TO PROJECT DEVELOPMENT - MASLAK, Olga; HRYSHKO, Natalia; HRYSHKO, Volodymyr; HLAZUNOVA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the volume and ratio of expenditures on scientific research and development in Ukraine, including agriculture, forestry, and fisheries. It identifies the direction and peculiarities of implementing research and development results in the agricultural sector. The work summarizes successful practices of implementing innovative projects by agribusiness enterprises and substantiates the importance of digital technologies in modernizing the industry, focusing on high-tech projects and technologies.To identify trends in labor productivity changes in enterprises engaged in agricultural activities in Ukraine, forecasting tools based on the extrapolation method (polynomial trend line) were applied. According to the forecasts of the Food and Agriculture Organization, an increase in crop yields (agriculture intensification) will be able to meet 90% of the demand for agricultural products by 2050. This target requires gradual productivity growth in the agricultural sector of 60%, which is unattainable without introducing an innovative development model for the agricultural sector. Data on Ukraine's food security situation indicate the relevance of issues related to stable food supply for the population in the long-term future.It is substantiated that the model of innovation-oriented development and modernization of the agricultural sector is based on a complex interaction of factors. Tools for building a Causal Loop Diagram were applied to determine the nature and characteristics of cause-and-effect relationships, clarify the potential for synergy, and the effects of balancing in cyclical chains. The causal loop diagram, which examines the feedback loops of the innovation-oriented agricultural development model, illustrates the formation of five cycles, three of which (R1, R2, R3) are reinforcing, and two others (B1, B2) are balancing. The study results show that the industry's innovative modernization processes should be based on cyclical improvement through the interaction of agro-innovation projects, digital solutions, ecological technologies, and energy efficiency. At the same time, to ensure the long-term development of the agricultural sector, it is necessary to maintain a balance between rapid innovation (reinforcing cycles) and environmental and economic sustainability (balancing cycles).
Keywords: innovative development models; scientific projects; development projects; agricultural sector; development strategy; scenario approach; innovation-investment projects; digitalization